SAT0038 Impact of Smoking on Remission Rates Differs Between Male and Female Rheumatoid Arthritis Patients: A Study Based on the Iorra (Institute of Rheumatology, Rheumatoid Arthritis) Cohort. (23rd January 2014) - Inoue, Y.; Tanaka, E.; Nakajima, A.; Inoue, E.; Kobayashi, A.; Hoshi, D.; Sugimoto, N.; Sugimoto, H.; Seto, Y.; Taniguchi, A.; Momohara, S.; Yamanaka, H.
Abstract : Background: Smoking is a known risk factor for developing rheumatoid arthritis (RA), and impacts the severity of RA or therapeutic response to RA. However, whether the impact of smoking on RA disease activity differs between men and women has not been fully investigated. Objectives: To investigate the effects of smoking on treatment status and remission rates, and to examine the gender difference cross-sectionally in Japanese patients with RA. Methods: The subjects were RA patients who participated in the IORRA survey during the month of April 2011, and for whom the following information was available: smoking status, rate of remission as defined by the Boolean-based remission criteria for clinical trials, and rate of remission as defined by Disease Activity Score in 28 joints (DAS28). Differences in serum levels of rheumatoid factor (RF), treatment status, and percentage of patients achieving remission according to each set of criteria were investigated between two groups: the Never smokers (group N) and current smokers (group C). Results: In the 3, 343 patients of group N (male; 162, female; 3, 181) or 524 patients of group C (male; 209, female; 315), the mean RF levels were significantly higher in group C for both sexes (males [N vs. C, 73.0 vs. 279.9 IU/ml, p<0.01], females [105.0 vs. 177.7 IU/ml, p<0.01]). No significant difference was observed when doses of methotrexate and corticosteroid, or rates of biologics use were compared between the two groups. In males, rate of remission as defined by the DAS28 (N vs. C, 63.0 vs. 49.8%, p<0.05) and Boolean-based remission criteria (36.4 vs. 25.8%, p<0.05) were significantly higher in group N. While in females, no significant difference was found in rate of remission as defined by Boolean criteria (N vs. C, 23.5 vs. 23.5%, p=0.993). Image/graph: Conclusions: The effects of smoking on remission rates differed between males and females. In males, never smokers showed significantly better remission rates than current smokers. References: Disclosure of Interest: Y. Inoue: None Declared, E. Tanaka: None Declared, A. Nakajima: None Declared, E. Inoue: None Declared, A. Kobayashi: None Declared, D. Hoshi: None Declared, N. Sugimoto: None Declared, H. Sugimoto: None Declared, Y. Seto: None Declared, A. Taniguchi: None Declared, S. Momohara: None Declared, H. Yamanaka Grant/research support from: Asahikasei Kuraray Medical Co., Ltd. Abbott Japan Co., Ltd. Asahikasei Pharma Corporation Astellas harma Inc. Astra Zeneca K.K. Bristol-Myers Squibb Chugai Pharmaceutical Co., Ltd. Daiichi Fine Chemical Co., Ltd. Daiichi Sankyo Co., Ltd. Dainippon Sumitomo Pharma Co., Ltd. Eisai Co., Ltd. GlaxoSmithKline K.K. Hisamitsu Pharmaceutical Co., Inc. Janssen Pharmaceutical K.K. Japan Tobacco Inc. Kaken Pharmaceutical Co., Ltd. Kissei Pharmaceutical Co., Ltd. Kowa Pharmaceutical Co., Ltd. Maruho Co., Ltd. Mitsubishi Chemical Medience Corporation Mitsubishi Tanabe Pharma Corporation Mochida Pharmaceutical Co., Ltd. MSD K.K., Mundipharma K.K. Nippon Chemiphar Co., Ltd. Nippon Shinyaku Co., Ltd. Novartis Pharma K.K. Otsuka Pharmaceutical Co., Ltd. Pfizer Japan Inc. Sanofi-Aventis K.K. Santen Pharmaceutical Co., Ltd. Sanwa Kagaku Kenkyusho Co., Ltd. Sekisui Medical Co., Ltd. Shionogi Co., Ltd. Taishotoyama Pharmaceutical Co., Ltd. Takeda Pharmaceutical Company Limited Teijin Pharma Limited Torii Pharmaceutical Co., Ltd. UCB Japan Co. Ltd. ZERIA Pharmaceutical Co., Ltd. Consultancies, speaking fee from Abbott, AstraZeneca, Bristol-Myers Squibb, Chugai, Eisai, Janssen, Mitsubishi Tanabe., Pfizer, Takeda, Teijin Pharma, UCB.